Reification, Matrices, and the Interrelationships of Goblin Spiders - Platnick, Norman I. (Zootaxa, 2013)
In a recent review of the interrelationships of goblin spiders (the family Oonopidae), Platnick et al. (2012) presented a new subfamily-level classification of the family, replacing older arrangements that included at least one paraphyletic group. That analysis was based heavily on new evidence obtained, by an international consortium of researchers, through scanning electron microscopy of the tarsal organs, tiny chemoreceptors found near the tips of the legs and pedipalps.